Inhibition of stem cell factor reduces pulmonary cytokine levels during allergic airway responses - BERLIN, A A (Blackwell Science Inc, 2004)
Stem cell factor (SCF) has a significant role in the inflammation and activation of allergic airway responses. When monoclonal anti-SCF was administered intratracheally during allergen challenge there was a significant alteration of eosinophil accumulation and airway hyperreactivity (AHR). Anti-SCF treatment also attenuated pulmonary cytokine and chemokine levels. In particular, there was an antibody dose-dependent decrease in interleukin (IL)-5 and tumour necrosis factor (TNF)-α. There was also a significant reduction of CCL2 and CCL5, which correlated with the reduction in AHR. Mice treated with anti-SCF demonstrated a significant decrease in pulmonary gob-5 gene expression, which has been shown to correlate to goblet cell hyperplasia/metaplasia relating to airway mucus production. Blocking SCF-mediated activation within the airway using a monoclonal antibody indicates that this cytokine may represent a viable target for therapeutic intervention that could affect multiple aspects of allergen-induced immunopathology.